Pengaruh Discovery Learning Berbantuan Simulasi PhET terhadap Minat dan Hasil Belajar Siswa SMPN 1 Siatas Barita pada Materi Getaran dan Gelombang - Sihotang, Johan; Sabani, Sabani (Journal of Natural Sciences, 2023)
This research aims to evaluate the impact of the Discovery Learning model using interactive PhET simulations on students' interest and learning outcomes at SMPN 1 Siatas Barita, particularly in the subject of Vibrations and Waves. PhET simulations incorporate animated and interactive elements, designed akin to games to facilitate exploratory learning for students. The research employed a Quasi-experimental method with a Non-Equivalent Control Group Design, where class VIII-1 served as the experimental group and class VIII-2 as the control group. The instruments utilized included learning tools, written tests, and questionnaires for data collection. Data analysis was conducted through hypothesis testing using Multivariate Analysis of Variance (MANOVA). The results revealed a significant influence of the Discovery Learning model assisted by PhET simulation on students' interest and learning outcomes in Vibrations and Waves at SMPN 1 Siatas Barita. Homogeneity analysis of the variance/covariance matrix indicated no variance matrix differences in the interest and learning outcomes of students between classes VIII-1 and VIII-2. The multivariate test results showed a low significance level, leading to the conclusion that the Discovery Learning model with PhET simulation assistance has a positive impact on students' interest and learning outcomes in the specified subject.